Envisioning a Reconceptualised Postgraduate Support in Research Writing Development for the Future: A Three-Legged Framework - Khumalo, Nonhlanhla Patience; Dongwe, †Khethiwe (African Journal of Inter/Multidisciplinary Studies, 2025)
The slow progress of postgraduate students in South African higher education institutions has been linked to a lack of preparedness at the undergraduate level, supervision practices and research writing skills of students. Academic departments and support units play a crucial role in facilitating the development of these students. However, the disconnect between the academic departments and writing centres is of great concern. The study aimed to determine how a collaborative student support initiative can be envisioned to assist postgraduate students in developing their research, academic writing and critical thinking skills. Drawing on the academic literacies lens that views writing and research as a social practice, the article reflects on postgraduate support, through collaborative engagement. The experiences of two academics, in introducing the Postgraduate Week initiative are presented. A lecturer in an academic department conceptualised this initiative. The implementation and facilitation were a collaboration involving this lecturer and the writing centre practitioner, in the same institution. Adopting an auto-ethnography reflective approach, the study interrogates reflections and practices analysed from individual journal entries. In line with auto-ethnography, the aim was to emancipate and transform staff and students so that they ripen as researchers. The paper highlights that interdisciplinary collaboration should be intentionally embedded and promoted to enhance students’ research writing development whilst incorporating humanising pedagogy and the lived experiences of university staff members. The article argues for pertinent opportunities for alternate ways to support postgraduate students. A Three-Legged framework is proposed, to highlight the importance of integrated tripartite postgraduate student support.